Carbonylation of C−N Bonds in Tertiary Amines Catalyzed by Low‐Valent Iron Catalysts. (3rd July 2019) - Nasr Allah, Tawfiq; Savourey, Solène; Berthet, Jean‐Claude; Nicolas, Emmanuel; Cantat, Thibault
Abstract: The first iron catalysts able to promote the formal insertion of CO into the C−N bond of amines are reported. Using low‐valent iron complexes, including K2 [Fe(CO)4 ], amides are formed from aromatic and aliphatic amines, in the presence of an iodoalkane promoter. Inorganic Lewis acids, such as AlCl3 and Nd(OTf)3, have a positive influence on the catalytic activity of the iron salts, enabling the carbonylation at a low pressure of CO (6 to 8 bars). Abstract : Kein Druck : Niedervalente Eisenkomplexe, wie z. B. K2 [Fe(CO)4 ], katalysieren effizient die Carbonylierung von C‐N‐Bindungen in Aminen durch CO‐Insertion. Lewis‐Säuren wie AlCl3 und Nd(OTf)3 haben einen positiven Einfluss auf die katalytische Aktivität und ermöglichen die Carbonylierung bei niedrigem CO‐Druck.